Institutional and economic determinants of Indian OFDI - Leena Ajit Kaushal (Cogent Economics & Finance)
The study explores the primary determinants of Indian OFDI in 26 developed and 81 developing countries by integrating a nuanced perspective of institutional distance with conventional location factors (2008–2018). Our findings indicate that asset augmentation and market-seeking motives are the primary OFDI drivers in developed and developing regions, respectively. Overall, the institutional environment demonstrates a positive association between Indian OFDI and the robust governance quality of the host country (excluding RS investments in developing region). However, only robust regulatory quality (RQ) & control of corruption (CC) are the primary IQ determinants significantly attracting OFDI in developed nations. Surprisingly, none of the WGI significantly drives OFDI in developing countries. However, the interaction effect reveals that only market-seeking investors from India are drawn to highly regulated (RQ), rule-based (RL) developing nations. The estimated FDI factors differ significantly depending on the destination, but RQ largely remains the crucial determinant across regions.